2010
DOI: 10.1016/j.bbr.2010.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of amygdaloid glutamatergic receptors on sensory and emotional pain-related behavior in the neuropathic rat

Abstract: The role of amygdaloid glutamatergic receptors (GluRs) in maintenance of the sensory versus emotional component of neuropathic pain was studied by assessing monofilament-induced limb withdrawal response (sensory pain) and aversive place-conditioning behavior (emotional pain) following amygdaloid administration of various glutamatergic compounds in nerve-injured animals. The results indicate that endogenous activation of amygdaloid group I metabotropic GluRs, mGluR(1) and mGluR(5), and the NMDA-R contributes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 14 publications
(22 reference statements)
1
36
0
Order By: Relevance
“…Injection of muscimol   Neuropathy- Reduced mechanical hyperalgesia- Decreased escape/avoidance[74] 3. Injection of NMDA antagonist   Neuropathy- Decreased pain-induced CPA[75] 4. Injection of group I mGluRs ligands   Naïve- Agonist induced visceral and mechanical hypersensitivity[76, 77]- Antagonist reduced visceral sensitivity  Formalin- Antagonist reduced mechanical hypersensitivity[77]  Arthritis- Antagonist reduced mechanical hypersensitivity- Antagonist decreased vocalizations[78]  Neuropathy- Agonist increased, and antagonist decreased, pain-induced CPA[75] 5.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Injection of muscimol   Neuropathy- Reduced mechanical hyperalgesia- Decreased escape/avoidance[74] 3. Injection of NMDA antagonist   Neuropathy- Decreased pain-induced CPA[75] 4. Injection of group I mGluRs ligands   Naïve- Agonist induced visceral and mechanical hypersensitivity[76, 77]- Antagonist reduced visceral sensitivity  Formalin- Antagonist reduced mechanical hypersensitivity[77]  Arthritis- Antagonist reduced mechanical hypersensitivity- Antagonist decreased vocalizations[78]  Neuropathy- Agonist increased, and antagonist decreased, pain-induced CPA[75] 5.…”
Section: Reviewmentioning
confidence: 99%
“…Injection of NMDA antagonist   Neuropathy- Decreased pain-induced CPA[75] 4. Injection of group I mGluRs ligands   Naïve- Agonist induced visceral and mechanical hypersensitivity[76, 77]- Antagonist reduced visceral sensitivity  Formalin- Antagonist reduced mechanical hypersensitivity[77]  Arthritis- Antagonist reduced mechanical hypersensitivity- Antagonist decreased vocalizations[78]  Neuropathy- Agonist increased, and antagonist decreased, pain-induced CPA[75] 5. Injection of group III mGluRs agonists   Naïve- Decreased mechanical sensitivity (mGluR7)- Decreased vocalizations and anxiety[79]  Arthritis- Increased mechanical sensitivity (mGluR8)- Increased vocalizations and anxiety[79] 6.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The amygdala consists of a number of nuclei, including the nucleus of the lateral olfactory tract, bed nucleus of the olfactory tract, anterior amygdaloid area, accessory basal nucleus, basal nucleus and lateral nucleus (Pitkä nen et al, 2000;de Olmos et al, 2004), and the amygdala has been linked to emotion (de Vito and Smith, 1982;Ansah et al, 2010;Ponomarev et al, 2010), memory (Maren, 1999;Savage and Guarino, 2010), sexual functioning (Carrer et al, 1973;Carrer, 1978;Holder and Mong, 2010) and neuroendocrine functioning Taleisnik, 1978, 1980). From the amygdala, the perirhinal cortex receives projections from the nucleus of the lateral olfactory tract, accessory basal nucleus, basal nucleus and lateral nucleus Price, 1974, 1977;McDonald and Jackson, 1987;Pikkarainen and Pitkä nen, 2001;Furtak et al, 2007b) with area 35 receiving the heaviest projections from the amygdala compared to area 36 and the accessory basal and lateral nuclei being the most prominent origins of these projections (Pitkä nen et al, 2000).…”
Section: Subcortical Afferents and Efferents Of The Perirhinal Cortexmentioning
confidence: 99%
“…Not surprisingly, human imaging studies have consistently shown that chronic pain activates the NAc [3, 4, 6]. At the circuit level, the NAc forms reciprocal projections with a number of regions critical for pain regulation including the amygdala, thalamus, prefrontal cortex (PFC) and hippocampus [1, 2, 32]. At the molecular level, opioid signaling in the NAc mediates placebo effects, whereas dopamine signaling has been shown to regulate descending inhibition, stress-induced hyperalgesia , and negative reinforcement from pain-relief [20, 38, 41, 48].…”
Section: Introductionmentioning
confidence: 99%